THE DEVELOPMENT OF MANUFACTURING INDUSTRY OF ANGOLA AS A FACTOR OF ENSURING THE COMPETITIVENESS OF THE COUNTRY’S ECONOMY - B. Sebashtiao (Вестник университета)
The article reveals the problem of the development of manufacturing industry in Angola as a factor of ensuring the competitiveness of the country’s economy. Scientific views on the concept “competitiveness” have considered. The state of competitiveness of the Angolan economy from the point of view of modern methodological approaches has analysed. The author identifies the reasons for lack of competitiveness of the Angolan economy on global competitiveness rankings, gives recommendations for the development of manufacturing industry in Angola as a mechanism to improve the competitiveness of the country’s economy. Besides this, the problems of public economic management in Angola have identified, which would be solving for the effective development of the manufacturing industry in the country.